2022
DOI: 10.1097/md.0000000000030754
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ruptured anterior communicating artery aneurysm treatment compared between surgical clipping and endovascular coiling: A single-center analysis

Abstract: The optimal treatment modality for ruptured anterior communicating artery (ACoA) aneurysms is unclear. Therefore, in this study, we aimed to compare the outcomes of endovascular coiling and surgical clipping to treat ruptured ACoA aneurysms. A retrospective analysis of 213 consecutive patients with ruptured AcoA aneurysms, who were treated with coiling or clipping between January 2010 and December 2020, was conducted. Of the 213 patients, 94 and 119 underwent clipping and coiling, respectively. The mean age wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Therefore, we conclude that EVT for ruptured AComA aneurysms offers a better functional outcome compared to MC. This finding aligns with a recent single-center analysis showing a 3-month favorable outcome rate of 73.1% in coiling group and 57.4% in clipping group ( p = 0.016) ( 4 ). Further multivariate analysis confirmed that coiling was an independent predictor of good outcomes in patients with ruptured AComA aneurysms (OR = 3.67, 95% CI: 1.70–7.90, p = 0.001) ( 4 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, we conclude that EVT for ruptured AComA aneurysms offers a better functional outcome compared to MC. This finding aligns with a recent single-center analysis showing a 3-month favorable outcome rate of 73.1% in coiling group and 57.4% in clipping group ( p = 0.016) ( 4 ). Further multivariate analysis confirmed that coiling was an independent predictor of good outcomes in patients with ruptured AComA aneurysms (OR = 3.67, 95% CI: 1.70–7.90, p = 0.001) ( 4 ).…”
Section: Discussionsupporting
confidence: 91%
“…This finding aligns with a recent single-center analysis showing a 3-month favorable outcome rate of 73.1% in coiling group and 57.4% in clipping group ( p = 0.016) ( 4 ). Further multivariate analysis confirmed that coiling was an independent predictor of good outcomes in patients with ruptured AComA aneurysms (OR = 3.67, 95% CI: 1.70–7.90, p = 0.001) ( 4 ). Similarly, the long-term outcomes of the International Subarachnoid Aneurysm Trial (ISAT) revealed that patients in the EVT group were more likely to be alive and independent at 10 years than those in the MC group (OR 1.34, 95% CI 1.07–1.67) ( 33 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Нині для лікування аневризм передньої сполучної артерії розроблено кілька нових хірургічних підходів [6,[11][12][13]:…”
Section: обговоренняunclassified